Differential Game Evading Strategy for a Flight Vehicle - Xie Jiliang, Ma Kemao (Hangkong bingqi)
In modern warfare, when it is being intercepted by an attacking missile, a flight vehicle has plenty ways to defend against the attacking missile, one of which is launching a defensive missile to intercept the attacking missile before the flight vehicle being intercepted. Based on differential game theory, this paper combines the advantages of norm-bounded and linear quadratic differential games and proposes a cost function which is segmented by relative distances between the players. Based on maximum principle, the equilibrium solutions of the differential game are obtained. And the equilibrium solutions, which can guarantee the maximum guidance performance of the flight vehicle are used as the guidance laws of the flight vehicle together with its defensive missile. It is difficult for the defensive missile to hit the attacking missile directly because the respective velocity and the maneuvering capability of the defensive missile is lower than that of the attacking missile. The guidance laws proposed in this paper guarantee that the defensive missile interferes the attacking missile and the flight vehicle has enough time to evade from the attacking missile. Simulation results verify the effectiveness of the design. The flight vehicle can be prevented being intercepted by the attacking missile regardless of whether the attacking missile takes the equilibrium solution as its guidance law.